2009
DOI: 10.2332/allergolint.08-oa-0023
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Induced Expression of CD203c on Basophils Predicts IgE-mediated Wheat Allergy

Abstract: Measurement of nOG-induced enhancement of CD203c on basophils is useful for the diagnosis of immediate wheat allergy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 27 publications
4
36
0
Order By: Relevance
“…The sensitivity and specificity of antigen-induced CD203c expression were reported to be 75 and 100%, respectively, in the diagnosis of latex allergy [8]. More recently, Tokuda et al [16] and Ocmant et al [17] published papers on the utility of food antigen-induced CD203c expression in the diagnosis of FA. Ocmant et al [17] reported that sensitivity and specificity of ovalbumin (OVA)-induced BATs applied to diagnose egg allergy were 62.5 and 96.4, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of antigen-induced CD203c expression were reported to be 75 and 100%, respectively, in the diagnosis of latex allergy [8]. More recently, Tokuda et al [16] and Ocmant et al [17] published papers on the utility of food antigen-induced CD203c expression in the diagnosis of FA. Ocmant et al [17] reported that sensitivity and specificity of ovalbumin (OVA)-induced BATs applied to diagnose egg allergy were 62.5 and 96.4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, BATs may be beneficial in the diagnosis of FA. In the study by Tokuda et al [16], measurement of purified native ω–5 gliadin-induced enhancement of CD203c on basophils is useful for the diagnosis of immediate wheat allergy in children. In the present study, we evaluated whether CD203c expression on basophils induced by food antigen would be useful in the prediction of OFC-associated symptoms in hen’s egg and milk allergies.…”
Section: Introductionmentioning
confidence: 99%
“…Basophil activation, in addition to activation of mast cells and other immune cells, and subsequent production of chemical mediators (such as histamine) can contribute to the initiation of anaphylaxis [12]. Basophils express the surface activation markers CD11b, CD63, CD123, CD203c and CD294, some of which previously have been shown to reflect allergen-dependent activation of basophils ex vivo [9,13,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…FA involves a double blind placebo controlled food challenge. It requires a control setting as the test has the potential to be dangerous [144,145].…”
Section: Functional Assays (Fa) or Food Challenge Testmentioning
confidence: 99%
“…FA involves a double blind placebo controlled food challenge. It requires a control setting as the test has the potential to be dangerous [144,145].Currently, the management of WA is based on avoidance of wheat. Patients should undergo dietary advice and referrals to identify relevant food allergens [146].…”
mentioning
confidence: 99%